A comunicação hipermidiática das comunidades jovens: caso Ragnarok on-line - Rabello, Ana Cristina Bariani Bica (2006)
The Massive Multiplayers On-line Game, a popularity worldwide communicational phenomenon are rapidly becoming an important socialization mechanism of all age people, nationality, ethnics and cultures. The object of this research is the Massive Multiplayer on-line Game Ragnarok on-line, an exclusive on-line game that has the constantly switch of information and ideas between players an essential condition for win. Analyze the communication interaction of societies build from these relations that can be producing new and challenging the actual rolls of social interaction and changing the verbal and non verbal dialog of communities in general. For participating communities, play by MMORPG can mean going in a complex social world, bringing together all of them real relationship problems and possibilities of problems existing in real life, possible by virtual representation of human figure. Analyze the relationship s characteristics of these communities, them building template, codes, representation systems and language adopted. Corpus of this analyze is constituted by interaction system made specifically in the game environment and implication about the communicational relationship pattern of these communities. The bibliography used evolve the know areas as follow: communication and information theory, communication media, theory of language, media studies, cyberculture, media culture, game theories